Reflection at work – A conceptual model and the meaning of its components in the domain of VET teachers - Hommel, Mandy; Fürstenau, Bärbel; Mulder, Regina H. (Frontiers in Psychology, 2023)
Professional development requires reflection. However, a conceptual model that considers the different perspectives on reflection remains missing. Regarding reflection, three different research streams can be distinguished: (I) an individual action-process-perspective, (II) a critical perspective, and (III) a social-relatedness perspective. From these three streams, important components are derived in the present study and integrated into one conceptual model. This model contains the individual and contextual components which influence reflection and considers reflection to be a process containing mutually influencing emotion, motivation, and cognition which can lead to various outcomes such as performance and, consequently, innovation. For illustrating the meaning of the model’s components in a specific professional context, we used data from an interview study with eight teachers of vocational schools. The conceptual model can serve as a basis for further research on reflection in all kinds of work contexts and be used to foster professional development, for instance by developing interventions to foster reflection.